Antibiotic prophylaxis against infective endocarditis after normal delivery--is it necessary?. Issue 5 (November 1980) - Sugrue, D; Blake, S; Troy, P; MacDonald, D
Abstract : During the years 1959 to 1978 inclusive 2165 women with rheumatic or congenital heart disease had vaginal deliveries at three large Dublin maternity hospitals. There were two (0.09%) cases of puerperal infective endocarditis, neither of which was unequivocally related to preceding childbirth during this period. Routine peripartum antibiotic prophylaxis was not given to either. A questionnaire of the practice of 19 obstetricians in Ireland showed that 12 (63%) gave antibiotics routinely during labour and after delivery in cardiac patients, five (26%) did not, and two (11%) used them occasionally. Peripheral vein blood was drawn serially from 0 to 30 minutes after vaginal delivery to determine the incidence of asymptomatic puerperal bacteraemia. A total of 299 cultures was obtained from 83 normal women and single blood cultures were positive in three women (3.6% of patients, 1.0% of cultures). A review of the published reports showed that well-documented cases of infective endocarditis and of asymptomatic puerperal bacteraemia after normal vaginal delivery are uncommon. There is evidence that antibiotic prophylaxis may increase the risk of developing antibiotic-resistant endocarditis. Recommended prophylactic regimens carry a considerable risk of drug toxicity. These facts, coupled with a lack of direct evidence in support of the efficacy of antibiotic prophylaxis, suggest that routine peripartum antibiotic prophylaxis is not indicated.